2017
DOI: 10.48550/arxiv.1706.02484
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the algebraic variety of Hom-Lie algebras

Elisabeth Remm,
Michel Goze

Abstract: The set HLie n of the n-dimensional Hom-Lie algebras over an algebraically closed field of characteristic zero is provided with a structure of algebraic subvariety of the affine plane K n 2 (n−1)/2 . For n = 3, these two sets coincide, for n = 4 it is an hypersurface in K 24 . For n ≥ 5, we describe the scheme of polynomial equations which define HLie n . We determine also what are the classes of Hom-Lie algebras which are P-algebras where P is a binary quadratic operads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In [72], the special cases of nilpotent and filiform Hom-Lie algebras are studied and classified up to dimension 7. In [73], the algebraic varieties of Hom-Lie algebras over the complex numbers are considered; it is shown that all 3-dimensional skewsymmetric algebras can be Hom-Lie algebras, but this is not true for the 4-dimensional case. Some more properties of the algebraic varieties of Hom-Lie algebras are studied.…”
Section: Introductionmentioning
confidence: 99%
“…In [72], the special cases of nilpotent and filiform Hom-Lie algebras are studied and classified up to dimension 7. In [73], the algebraic varieties of Hom-Lie algebras over the complex numbers are considered; it is shown that all 3-dimensional skewsymmetric algebras can be Hom-Lie algebras, but this is not true for the 4-dimensional case. Some more properties of the algebraic varieties of Hom-Lie algebras are studied.…”
Section: Introductionmentioning
confidence: 99%